Controladores robustos adaptativos para um conversor trifásico a três fios conectado à rede com filtro LCL - Evald, Paulo Jefferson Dias de Oliveira (2021)
This work presents new robust adaptive control strategies of adaptive robust controllers, in discrete time, applied to the grid-injected currents control of a voltage-fed three-phase three-wires static converter connected to the electrical grid with LCL ﬁlter. The application of adaptive controllers on grid-tied converters is justiﬁed due to the uncertainties and pa- rametric variations inherent to the grid impedance. However, typically, adaptive controllers based on a reference model implemented for this application are complexes, because the reference model need to has the same relative degree of modelled part of the plant, which is equal to three, in continuous time, or relative degree equal to two, if discretised consi- dering implementation delay. It implies on a complex control design and will require a high processing capacity from microcontroller to execute it. Thereby, initially an order reduction of LCL ﬁlter model is proposed, where is demonstrated mathematically that ﬁlter capacitor can be considered as an unmodelled dynamics of additive type, resulting in an ﬁrst order model. With this, it is possible to design a robust adaptive controller with a ﬁrst order re- ference model, since the relative degree of the modelled part of the plant is one. Next, two new robust adaptive controllers are proposed, entirely in discrete time. The ﬁrst new strategy, PI-RMRAC, is a robust PI (Proportional-Integral) controller based on a reference model. This new control approach is a reformulation of the parameter vector, which, like the previous strategy, is based on a ﬁrst-order reference model. The second proposed new controller, a robust adaptive PI controller, tracks straightforwardly the reference currents, consequently it does not require the reference model implementation, further simplifying the controller design. In this controller, the identiﬁcation of adaptive gains is equivalent to estimate, indirectly, the closed-loop system gains. Furthermore, the stability and robustness proofs of controllers, in discrete time, are presented. In addition, to corroborate the propo- sed strategies performance, the experimental results are compared with a robust adaptive controller with a third-order reference model.